(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A feminist reading involves a close examination of the way the female characters are portrayed in a work of literature as the feminist critics consider literature to be an important tool of socialization. Looking at Fire on the Mountain from a feminist perspective, one finds that Anita Desai has scored indeed high in the creation of her female characters. The tale starts with Nanda Kaul living alone at Carignano, joined by Raka, her great granddaughter and Ila, her friend. The novel ends with the rape and murder of Ila. Instead of creating female stereotypes that fit into the social mould of perfect women, Anita Desai has created real women, complete with their strengths and weaknesses, virtues and foibles. The three protagonists are all women of substance who face their life with grace and dignity.